The effectiveness of motivational interviewing on the oral health of leukemic children and oral health care knowledge, attitude and practice of their mothers: a hospital-based intervention - Niloofar Falahinia; Samaneh Razeghi; Ahmad Reza Shamshiri; Manijeh Firoozi; Simin Zahra Mohebbi (BMC, 2023)
Abstract Background Some studies suggest a higher effectiveness of motivational interviewing compared to common oral health instruction in healthy individuals. As regards to higher prevalence of dental diseases like early childhood caries, oral mucositis, and gingivitis are reported for leukemic children, the present study aims to compare the effectiveness of educating mothers through MI with the common instruction (CI) for the oral health of children with leukemia under six years old. Method This quasi-experimental study was designed in Tehran University of Medical Sciences, School of Dentistry and conducted on 61 mothers with leukemic children under age six hospitalized in Mahak Hospital and Rehabilitation Complex which is a Pediatric Cancer Research and Hospital Center, in 2021. Mother and child pairs were allocated to MI or CI (using pamphlets) groups. Data was collected using a questionnaire of mothers' knowledge, attitude, motivation, and practice concerning oral health care in leukemic children. The children underwent clinical examination to assess plaque index before and three months after the intervention. The data were analyzed using SPSS version 25 (IBM, Armonk, NY, USA) by ANCOVA test. Results The preschoolers mean ages were 4.23 ± 1.41 and 4.32 ± 1.33 (ranged from 2 to 6 years old) in the MI and CI group, respectively. There were 16 girls (53.3%) and 14 boys (46.7%) in the MI group, and 15 girls (48.4%) and 16 boys (51.6%) in the CI group. Significant differences were observed in the amount of plaque index between the MI group and the CI group (0.20 ± 0.04, p-value < 0.001). A significant increase was observed in the mean of changes in scores of knowledge, attitude, motivation, mother's practice concerning child's oral health, mother's practice concerning personal oral health in the MI group (p-value < 0.001). Conclusions Considering that instruction using MI showed to be effective in improving oral health adherence in mothers and reducing plaque in children with Leukemia, it may be recommended as a promising method to promote the oral health of such susceptible children in places that they are constantly present for treatment. Trial registration The study was registered in the Iranian Registry of Clinical Trials (IRCT) on 11.03.2021 (code: IRCT20131102015238N5).